Is decreased hip flexibility a risk factor of arm injuries in young baseball players? Systematic review and meta-analysis - Ueda, Y.; Taniguchi, M.; Noda, T.; Minaguchi, S.; Ichihashi, N. (Clinical Journal of Sport Medicine, 2025)
Objectives: Although various kinematic parameters have been investigated as factors associated with shoulder and elbow injuries during pitching, the relationship between lower extremity flexibility and such injuries remains unclear. The objective of this meta-analysis was to examine the association between pitching injuries to the shoulder and elbow and lower extremity flexibility.